Kungfu/wushu in the promotion of China`s culture and image - Ciembroniewicz, Ewa (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Sport is a specific form of human activity, contingent on the political and socio-cultural history of a given region/state, strengthening national identity and sense of the distinctiveness of entities living in that region or state. At the same time, it has an unquestionable influence on the process of building and strengthening the country`s image in the international arena.
Keywords: Chinese martial arts; kungfu/w?shu; cultural diplomacy; sports diplomacy; public diplomacy; international image